The product avatar as a product-instance-centric information management concept. (9th October 2006) - Hribernik, K.A.; Rabe, L.; Thoben, K-D.; Schumacher, J.
This paper presents the concept of semi-autonomous product-centric information management based on the Product Avatar (PA) concept, discussing the overall concept of distributed and decentralised information management relevant to individual product items and analyses the requirements the concept generates. In that context, it aims at stimulating discussion on the pragmatic utilisation of emerging technologies, such as RFID, wireless networking and ubiquitous computing. This paper further illustrates the benefits of the application of the PA concept in examples related to PLM against a scenario based on a network of organisations connected to the maintenance, repair and operation processes of a product.